KAJIAN SPEKTRA IR DAN AAS LEMPUNG TERPILARâFe - Ritonga, Pangoloan Soleman (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2012)
It has been successfully synthesized a new pillared clay adsorbent by using natural bentonite from the Kecamatan Tulakan Pacitas East Java. The synthesis was carried out by intercalation methode by mixing benzalkonium chloride surfactant solution and precursor solution of iron chloride into natural bentonite solution, then the resulted solid phase was calcined at 400oC. The natural bentonite and the adsorbent of pillared clay were characterized by using infra red spectrosphotometer. The iron oxide content was determined by using atomic absorption spectroscopy. It has been concluded that pillarization proses increased the iron oxide content up to five time depending on the mole ratio of iron and cation exchange capacity (CEC) value of natural bentonite. From infra red spectra, it has been concluded that surfactant intercalation into inter layer space can be observed by using peak at 2925.8 and 2852.5 cm-1, while the iron oxide pillared is not observed.